2012
DOI: 10.1007/s11695-012-0733-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Influence of Whole and Defatted Flaxseed on Satiety, Glucose, and Leptin Levels of Women in the Late Postoperative Stage of Bariatric Surgery

Abstract: Whole flaxseed and defatted flaxseed did not promote satiety in women in the late postoperative of RYGBP. However, the test meals with a lower fat content increased the serum leptin levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Moreover, one study was done on children (Gholami & Akhlaghi, 2021), while the other's participants were adults. As presented in Table 1, four studies were conducted in Brazil (Candido et al, 2018; Cohen et al, 2013; Cosendey Menegati et al, 2012; Monteiro et al, 2016), three in Denmark (Ibrugger et al, 2012; Kristensen et al, 2012, 2013), two in the UK (Almehmadi et al, 2018; Lakhani & Ibrahim, 2016), and one study in each country of USA (Lafond et al, 2015), India (Kapoor et al, 2017), Iran (Gholami & Akhlaghi, 2021), and Canada (Vuksan et al, 2017). In different studies, the sample size of the intervention group ranged from 6 to 65 and the mean age of the intervention group ranged from 22.5 to 48.3 years old in adults studies and 11.5 years old in the study done on children and adolescents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, one study was done on children (Gholami & Akhlaghi, 2021), while the other's participants were adults. As presented in Table 1, four studies were conducted in Brazil (Candido et al, 2018; Cohen et al, 2013; Cosendey Menegati et al, 2012; Monteiro et al, 2016), three in Denmark (Ibrugger et al, 2012; Kristensen et al, 2012, 2013), two in the UK (Almehmadi et al, 2018; Lakhani & Ibrahim, 2016), and one study in each country of USA (Lafond et al, 2015), India (Kapoor et al, 2017), Iran (Gholami & Akhlaghi, 2021), and Canada (Vuksan et al, 2017). In different studies, the sample size of the intervention group ranged from 6 to 65 and the mean age of the intervention group ranged from 22.5 to 48.3 years old in adults studies and 11.5 years old in the study done on children and adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the increasing research studies on the seed of flax in the last decade, there seem to be inconsistencies between previous studies evaluating its effects on appetite and/or satiety. Some trials suggested an inverse relationship between flaxseed intake and appetite (Ibrugger, Kristensen, Mikkelsen, & Astrup, 2012; Kristensen et al, 2013; Lakhani & Ibrahim, 2016; Monteiro, Rosa, Luiz, Neto, & Oliveira, 2016; Vuksan et al, 2017), while others showed no effects of flaxseed consumption neither on appetite nor on satiety compared with control groups (Almehmadi, Lightowler, Clegg, & Chohan, 2018; Candido et al, 2018; Cohen et al, 2013; Kristensen et al, 2012; Lafond, Greaves, Maki, Leidy, & Romsos, 2015; Vuksan et al, 2017). Therefore, we aimed to assess this relationship more precisely and conclusively in a systematic review of clinical trials on humans for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…Our search retrieved 613 articles; after removing duplicates, 127 articles were remained. After screening titles/abstracts, 22 related articles were carefully assessed for the eligibility . After taking exclusion criteria into account, fourteen RCTs were remained to be included in the current systematic review .…”
Section: Resultsmentioning
confidence: 99%
“…Among adipokines secreted by adipose tissue, human leptin has recently attracted scientists because of its various hormonal functions . It is shown that leptin affects long‐term energy balance regulation and suppresses food intake, thus may induce weight loss . Furthermore, it is proposed that leptin may impress circulatory system, surfactant activity of lungs, fertility, brain and also bones .…”
Section: Introductionmentioning
confidence: 99%
“…As described [24,25,26], VAS was adopted to determine hunger, fullness, satisfaction and prospective food intake. Subjects were familiarized with this scale before the tests.…”
Section: Methodsmentioning
confidence: 99%